Morphometric and Immunohistochemical Characteristics of the Adult Human Soft Palate Muscles. (March 2022) - Mu, Liancai; Chen, Jingming; Nyirenda, Themba; Li, Jing; Sobotka, Stanislaw; Benson, Brian; Christopherson, Mark; Sanders, Ira
The soft palate is the only structure that reversibly separates the respiratory and gastrointestinal systems. Most species can eat and breathe at the same time. Humans cannot do this and malfunction of the soft palate may allow food to enter the lungs and cause fatal aspiration pneumonia. Speech is the most defining characteristic of humans and the soft palate, along with the larynx and tongue, plays the key roles. In addition, palatal muscles are involved in snoring and obstructive sleep apnea. Considering the significance of the soft palate, its function is insufficiently understood. The objectives of this study were to document morphometric and immunohistochemical characteristics of adult human soft palate muscles, including fiber size, the fiber type, and myosin heavy chain (MyHC) composition for better understanding muscle functions. In this study, 15 soft palates were obtained from human autopsies. The palatal muscles were separated, cryosectioned, and stained using histological and immunohistochemical techniques. The results showed that there was a fast type II predominance in the musculus uvulae and palatopharyngeus and a slow type I predominance in the levator veli palatine. Approximately equal proportions of type I and type II fibers existed in both the palatoglossus and tensor veli palatine. Soft palate muscles also contained hybrid fibers and some specialized myofibers expressing slow-tonic and embryonic MyHC isoforms. These findings would help better understand muscle functions.